Next-generation sequencing and comparative analysis of Pyrrhocorax pyrrhocorax and Pyrrhocorax graculus (Passeriformes: Corvidae) mitochondrial genomes. (3rd May 2016) - Morinha, Francisco; Clemente, Carla; Cabral, João A.; Lewicka, Magdalena M.; Travassos, Paulo; Carvalho, Diogo; Dávila, José A.; Santos, Mário; Blanco, Guillermo; Bastos, Estela
Abstract: The complete mitochondrial genomes of Red-billed Chough ( Pyrrhocorax pyrrhocorax ) and Yellow-billed Chough ( Pyrrhocorax graculus ) were sequenced using the Ion Torrent PGM platform. These mitogenomes contain 16, 889 bp (Red-billed Chough) and 16, 905 bp (Yellow-billed Chough), including 13 protein-coding genes (PCGs), two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and a control region (D-loop). The gene content, orientation, and structure are similar to a wide range of other vertebrate species and the nucleotide composition is very similar to other Passeriformes. All PCGs start with ATG, except for COX1 that starts with GTG, and four stop codons and one incomplete stop codon are used (TAA, TAG, AGG, AGA, and T-). The size of PCGs is the same in both mitogenomes, except for ND6 that has one codon less in the Yellow-billed Chough. All the tRNAs can fold into a typical cloverleaf secondary structure. These mitogenomic data can be of great value in complementing forthcoming approaches on molecular ecology, comparative and functional genomics.